Real-time damage assessment of hydrous sandstone based on synergism of AE-CT techniques. (September 2018) - Tao, Kai; Zheng, Wei
Abstract: Sandstone exists widely in nature. The good permeability of hydrous sandstone makes it prone to collapse, which can cause natural disasters. Hence, studies into damage assessment of hydrous sandstone are crucial. Moisture is an important factor in sandstone structural damage. The major damage assessment methods of hydrous sandstone at present cannot satisfy real-time and portability requirements. In this study, acoustic emission (AE), computed tomography (CT), and electroencephalogram (EEG) techniques are combined for real-time damage assessment of hydrous sandstone. First, a real geotechnical engineering environment is simulated, and the AE signal stimulated from hydrous sandstone under gradually changing loading is analyzed. A mapping method of AE and moisture is proposed using the support vector machine algorithm. Second, a comprehensive damage assessment method is developed based on the CT technique. The mapping rule between moisture and damage level is determined through a model experiment. Third, a real-time damage assessment function of hydrous sandstone is proposed by considering two pieces of information: the assessment level of single AE, which varies with time, and the superposition effect of many AE events. Lastly, eight visual colors for warning are screened according to different damage states, and an EEG experiment is conducted to demonstrate their diverse excitations of the human brain's concentration. Highlights: AE, CT, and EEG techniques are combined for damage assessment of hydrous sandstone. A comprehensive index damage assessment method is developed based on CT techniques. EEG technique is conducted to demonstrate different color's diverse excitations. Real time and portability requirements in structural monitoring can be met.